Clinical implications of predominant polarity and the polarity index in bipolar disorder: a naturalistic study. (19th July 2013) - Popovic, D.; Torrent, C.; Goikolea, J. M.; Cruz, N.; Sánchez‐Moreno, J.; González‐Pinto, A.; Vieta, E.
<x xml:space="preserve">Abstract</x> Objective Predominant polarity (PP) is an important variable in maintenance treatment of bipolar disorder (BD). This study aimed at determining the role of polarity index (PI), a metric indicating antimanic versus antidepressive prophylactic potential of drugs, in clinical decision‐making. Method Two hundred and fifty‐seven of 604 (43%) of patients with BD‐I or II fulfilled criteria for manic (MPP) or depressive PP (DPP). The PI, representing the ratio of number needed to treat (NNT) for depression prevention to NNT for mania prevention, was calculated for patients' current treatment. MPP and DPP groups were compared regarding sociodemographic, clinical and therapeutic characteristics. Results One hundred and forty‐three patients (55.6%) fulfilled criteria for DPP and 114 (44.4%) for MPP. Total PI, Antipsychotics' PI, and mood stabilizers PI were higher, indicating a stronger antimanic action, in MPP. MPP presented higher prevalence of BD‐I, male gender, younger age, age at onset and at first hospitalization, more hospitalizations, primary substance misuse, and psychotic symptoms. DP correlated with BD‐II, depressive onset, primary life events, melancholia, and suicide attempts. Conclusion The results confirm the usefulness of the PI. In this large sample, clinical differences among these groups justify differential treatment approach. The PI appears to be a useful operationalization of what clinicians do for maintenance therapy in BD.